Cyber aggression: Moderating effects of out group prejudice on the relation between threat perceptions - Mardianto, Mardianto; Mudhar, Mudhar; Ifdil, Ifdil; Ardi, Zadrian; Magistarina, Elrisfa (International Journal of Research in Counseling and Education, 2022)
Cyber aggression has become a very troubling social problem. This phenomenon is an interaction problem between individuals and groups in cyberspace. This study aims to examine the role of perceived threat mediated by prejudice against cyber-aggression by Indonesian youth. The method used in this study is a quantitative survey with structural equation modelling analysis, namely the Structural Equation Model (SEM). The sample in this study used a purposive sampling technique, with 1118 teenagers as respondents from several cities in Indonesia, using techniques of web-based self-report personality scales. The results show that the theoretical model of adolescent cyber-aggression behavior is in accordance with empirical conditions in the field because it meets the goodness of fit model standard, meaning that the perception of threats mediated by prejudice is simultaneously proven to contribute to adolescent cyber-aggression behavior.